P187 Paratracheal abscess by plant fungus Chondrostereum purpureum. First case report of human infection. (20th September 2022) - Dutta, Soma; Ray, Ujjwayini
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objective: To identify the etiological agent of paratracheal abscess applying molecular techniques. Methods: A 61-year-old male, plant Mycologist, who specially works with mushrooms presented to the OPD with hoarseness of voice and difficulty in swallowing for the last 3 months. CT scan demonstrated the presence of a right paratracheal abscess. CT-guided aspiration of the abscess was performed. The pus was sent for microbiological evaluation. Results: The pus culture done on Sabouraud dextrose agar grew a creamy pasty colony with buff-colored pigmentation on reverse side (Fig. 1). On LCB mount preparation it was found to be a yeast-like structure with slender hyphae as shown in Fig. 2. The fungus could not be identified phenotypically, so it was sent to the 'WHO Collaborating Centre for Reference and Research on Fungi of Medical importance'. It was identified as Chondrostereum purpureum by DNA sequencing. Patient was treated with oral voriconazole following drainage of the pus and the outcome was favorable. The patient denied having worked with such a plant pathogen but he confirmed d that he was working with decaying material and other plant fungi for a long time as part of his research activities. Conclusion: Silver leaf is a fungal disease of trees caused by the fungus plant pathogen Chondrostereum purpureum. The disease is progressive and often fatal for the plants. It is spread by airborne spores landing on freshly exposed sapwood. No human infection was reported till date. The case report demonstrates the crossover of plant pathogens into humans when working in close contact with plant fungi.